Legal regulation of free legal aid providing - Strukova, Kristina (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
In the article, the author examined the concept and essence of and legal support of the system of legal aid providing in Ukraine via analyzing practice of the institutions of legal aid providing. The author analysis the current law in the field of providing legal aid. The author described the peculiarities and nature of the legal features of providing primary and secondary free legal aid. Also author described distinction between features of legal support of primary and secondary legal aid in the context of the provision of legal services